ABILITY OF MATHEMATICAL REPRESENTATION JUNIOR HIGH SCHOOL STUDENTS IN COMPLETING OPEN-ENDED PROBLEMS ARE REVIEWED FROM THE STYLE OF THINKING - Widiyastuti, Erni; Ernawati, Nur; Setyaningsih, Eka; Sugihandardji, Chumaedi (International Journal of Multidisciplinary Research and Literature, 2022)
Mathematical representation is how a person communicates the mathematical ideas in question to others. This ability has an important role in learning mathematics, especially as a foundation to align problem solving. This study aims to describe the mathematical representational ability of junior high school students in solving open-ended problems. The study subjects were students of grade XI junior high school. This research is qualitative descriptive research. Taking subjects using purposive sampling, which is based on their thinking style. Data collection uses tests, questionnaires, and interviews. The results showed that the ability of mathematical representations of: (1) groups of students of concrete sequential thinking styles able to create and communicate mathematical ideas in the form of images, have not been able to make mathematical models perfectly and are sufficiently able to use written words or text; (2) groups of students of abstract sequential thinking styles are less able to create and communicate mathematical ideas in the form of drawings but able to create mathematical models of ideas or ideas and are sufficiently able to use written words or text; (3) groups of students of abstract random thinking styles are less able to create and communicate mathematical ideas in the form of drawings and create mathematical models of ideas or ideas, but are sufficiently able to use written words or text; (4) Groups of students of concrete random thinking styles are quite capable of creating and communicating mathematical ideas in the form of drawings, unable to create mathematical models of ideas or ideas, less able to use written words or text